Rising colorectal cancer burden attributable to high body mass index in China from 1990 to 2021: a comprehensive analysis using the global burden of disease study - Chen, Xiamei; Chen, Bijuan; Ye, Sufang; Lin, Hui; Yang, Chunkang; Zhan, Zhouwei (Frontiers in Endocrinology, 2025)
BackgroundColorectal cancer (CRC) attributable to high body mass index (BMI) has become a significant public health issue in China. This study analyzes the burden of CRC attributable to high BMI from 1990 to 2021, exploring trends in mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs).MethodsData were obtained from the Global Burden of Disease Study (GBD) database. Age- and sex-specific mortality, DALYs, YLDs, and YLLs rates were analyzed for 2021, and temporal trends were examined from 1990 to 2021. Joinpoint and age-period-cohort (APC) analyses were conducted to identify shifts in burden and contributing factors. Decomposition analysis was applied to assess the impact of aging, population growth, and epidemiological changes.ResultsIn 2021, 19,418 CRC deaths were attributable to high BMI in China, with a higher burden observed in males. The total DALYs reached 507,316, and YLLs accounted for 482,925. From 1990 to 2021, age-standardized mortality rates increased by 2.43-fold, while DALYs and YLLs increased by 2.33-fold and 2.24-fold, respectively. The most dramatic increase was seen in YLDs, with a 5.17-fold rise. Epidemiological changes contributed most to the increases in deaths and DALYs, followed by aging, while population growth had the least impact.ConclusionsThe burden of CRC attributable to high BMI in China has grown significantly over the past three decades, with males disproportionately affected. Aging and epidemiological changes are the main drivers of this trend, underscoring the need for targeted interventions to reduce the CRC burden.